Ivan Svitlychnyj’s Language Personality through the Prism of His Epistolary: Psycholinguistic Aspects (Linguostylistic Studies, 2022)
Aim of the research. Case study of the issue is based on the epistolary of I. Svitlychny – poet, translator, and subtle connoisseur of the word. In the focus of the analysis are the selected pages of his correspondence with friends and colleagues,  both in Ukraine and the Diaspora. Research methods. The article provides explanation of the research methodology, namely, the descriptive, functional-stylistic, and comparative methods used in the analysis of Ivan Svitlychny’s epistolary texts and the memoirs of his associates. The above methods make it possible to perceive the text’s integrity (textual semantics) and explain the coherence of the material (the meaning of the text), the task of which is to reveal the intrathecal features of the epistolary of a famous dissident. The study of extralinguistic intentions of the represented text of Ivan Svetlichny involves also the method of discourse analysis, which sheds light on the external factors that influence the cognitive component of the verbal picture of the writer’s individual style. Results. Ivan Svitlychny’s epistolary creativity concentrates around important social, moral, and ethical ideals of modernity, revealing the depth of thinking, sharpness of worldview, and ability to skillfully convey the inner world of man. The artistic perfection of individual speech, the aesthetic taste are manifested in the choice of lexical means of expressionI. Svitlychnyk’s language contains a considerable amount of expressive vocabulary, which is used as a stylistic attribute to his individual style. One of the decisive factors influencing the functioning of special forms in epistolary text is the individual author's style, the general concept, and the ideological and aesthetic orientation of the writer's work. The study of I. Svetlichny’s letters allows to consider the use of lexical means as a single stylistic complex, formed not only by objectively defined properties of words, but also by their subjective authorial interpretation, which is an essential aspect in the context analysis. Conclusion. The analysis of the process of I. Svitlychny’s personality formation provides clues to distinguishing the following factors that determined the linguistic and psychological features of the writer and scientist's linguistic nature: comprehensive erudition, high-quality education, received at the Kharkiv University, postgraduate studies at the Institute of Literature of NAS of Ukraine; communication with peasants, workers, the repressed; long-term editorial activity; genuine linguistic sense and intuition, individual-language practice in four functional styles (artistic, scientific, journalistic, epistolary); activities on editing and refining the Dictionary of Synonyms of the Ukrainian Language; participation in the socio-political dissident movement of the Sixties.
Keywords: label formulas; copyright neologisms; sixties; language signs; psycholinguistic portrait